Prohibition : social movement and controversial amendment - Stoltman, Joan (American history (Lucent Books), 2019)
Examines the history of Prohibition beginning in colonial times through the aftermath of Prohibition and the passing of the Twenty-first Amendment. Includes tables, a timeline, resources for further information, and archival photographs.